Consumer Credit and the Incidence of Tariffs: Evidence from the Auto Industry - Hankins, Kristine W.; Momeni, Morteza; Sovich, David (American Economic Review, 2026)
Captive finance subsidiaries create a channel for trade policy to affect consumer credit. Examining the impact of the Trump administration’s metal tariffs on captive automobile lenders, we find that consumers received higher interest rates from captive lenders after the tariffs relative to unaffected noncaptive lenders. Further, we document a disparate impact on low-income borrowers and in areas with less lending competition. Our results suggest that tariffs may impact not only the price of goods but also the financing terms of purchases. Thus, focusing solely on directly affected product prices may underestimate tariff pass-through significantly. (JEL F13, F14, G21, L22, L61, L62)